Visual Research Methods in Educational Research - Moss, Julianne; Pini, Barbara; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
.
Keywords: Social sciences; Communication; School management and organization; School administration; Educational sociology; Educational technology; Education and sociology; Sociology, Educational; Social Sciences; Methodology of the Social Sciences; Administration, Organization and Leadership; Technology and Digital Education; Sociology of Education; Sociology of Education; Media Studies; Electronic books